2015
DOI: 10.3390/su70810521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Economic Efficiency of Apple Orchard Investments

Abstract: Abstract:The tree-growing sector is considered to be an important supplier of food and raw material for industry worldwide. Increasingly competitive decisions regarding international investment in orchards depend on business analysis. This study compares three apple orchards situated in Cluj-Napoca, on the Eastern limits of the Transylvanian Plain, Romania. While the climatic and soil conditions are relatively consistent among the three orchards, the technical and economic results (expressed in hectares) vary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…4 x 2 m). Mean plot size was 1558 m, and the mean rootstock population was 194 rootstocks per plot. The age of the plots varied between 20 and 23 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 x 2 m). Mean plot size was 1558 m, and the mean rootstock population was 194 rootstocks per plot. The age of the plots varied between 20 and 23 years.…”
Section: Methodsmentioning
confidence: 99%
“…As trees get depleted and production declines, the old orchard is terminated and a new one is replanted. Frequent turnover requires that orchard termination costs are minimized, so that they do not weigh too much on the financial performance of the operation . Hence, the strong interest in finding cost‐effective termination practices that may reduce the strain on farmer resources.…”
Section: Introductionmentioning
confidence: 99%
“…After %5 years, 'Honeycrisp' with TS (3230 trees/ha) on 'B.9' had a positive NPV in our study, whereas 9 years were needed when planting 539 trees/ha on 'M.M.111'. Similarly, in a study of Badiu et al (2015) in Romania, 4 years were reported to payback with high-density plantings (3175 trees/ha), whereas up to 10 years were needed for low densities (333 trees/ha); however, payback is not perfectly comparable with NPV because the former does not consider an investment recoup with interest.…”
Section: Discussionmentioning
confidence: 98%
“…Given that MOE are taken from early studies of performance evaluation, it is reasonable to point the discussion about this concept starting from Levis at MIT (Levis, 1986) and further such as Waltz and Llinas (Hall, 1992). The term MOE has more recently been used to indicate measures of performance (Green and Johnson, 2002;Badiu et al, 2015) as well as customer satisfaction or compliance (Laere, 2009). It has been also used anywhere in a system and at any level, insofar as a customer has corresponding requirements.…”
Section: Introductionmentioning
confidence: 99%